2007
DOI: 10.2754/avb200776040509
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Rabbit Pancreas with Particular Regard to the Argyrophilic Cells

Abstract: Titlbach M., E. Maňáková: Development of the Rabbit Pancreas with Particular Regard to the argyrophilic Cells. acta vet. Brno 2007, 76: 509-517.The aim of the study was the description of the prenatal development of rabbit pancreas, cell modifications, and changes in their volume and mitotic activity.immunohistochemical, light and electron microscopic procedures were employed. Stereological methods were used for estimation of cellular and nuclear volumes. hits on epithelial cells, tubular lumens, and endocrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
5
2
0
Order By: Relevance
“…On the other hand, the smaller ducts consisted of squamous principal cells. This is similar to the embryonic pancreas of other vertebrate species (Hick et al, ; Laitio et al, ; Pictet & Rutter, ; Titlbach & Maňáková, ; Villasenor et al, ).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…On the other hand, the smaller ducts consisted of squamous principal cells. This is similar to the embryonic pancreas of other vertebrate species (Hick et al, ; Laitio et al, ; Pictet & Rutter, ; Titlbach & Maňáková, ; Villasenor et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…It can be assumed that the abundant mitotic divisions of pancreatic duct cells in Natrix are correlated with the growth of the pancreas and their tubular branching. Similar mitotic divisions were also described in the pancreatic duct cells of chick (Zeigel, ), rabbit (Titlbach & Maňáková, ), and rat (Pictet & Rutter, ) embryos.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In literature, prenatal development of exocrine pancreas has been reported in rat [ 3 ], pig [ 4 ], sheep [ 5 ], rabbit [ 6 ], and human [ 7 , 8 ], but very scanty literature is available in buffaloes [ 9 , 10 ]. So the present research work was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study fused definitive pancreas was first observed at 53 days gestation. Two primordia of pancreas were fused together at 7 th week of gestation in man (Arey, 1954) and 15 th day of gestation in rabbit (Titlbach and Manakova, 2007). In goat foeti the pancreas lied in the abdominal cavity partly on right and partly on left side of median plane.…”
Section: Resultsmentioning
confidence: 99%